Technological mindfulness and work-life balance - Yusasniza Mohd Yunus; Mohd Zaher Mohd Zain; Aini Aman (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study examines the impact of technological mindfulness on work-life balance among accountants in the Klang Valley, Malaysia. Mindfulness is defined as constantly aware of what we are doing, aware of the consequences of actions, and able to observe the stimuli without reliance on the outdated category of actions that may reduce users’ attention level. The power of mindfulness in information system (IS) use in the workplace should enhance the outcome of users’ behaviour and work-life balance. It is fairly well understood that when work and personal life are out of balance, the stress level is likely to increase. Employees tend to bring their work home, work for long hours, and that has caused negative outcomes. For example, accountants are exposed to acute demands of services in dealing with changes and forces in business life as a result of globalisation. Underutilising the benefits of IS could impact accountants’ credibility and reputation. This study intends to explore the practices of mindfulness in IS and its impact on work-life balance. In general, the qualitative methodology was employed using case study and interviews. In selecting the cases to be included in the study, attempts were made to include accountants that use IS as mandatory in IS-intensive organisations. A set of interview questions was prepared and interviews were conducted. The findings revealed that learning and practice, knowledge sharing, IS features exploration, high visualisation, reflective thinking, creative thinking, coaching and training are some of the practices of technological mindfulness. These practices have helped IS users to be more efficient and effective in the workplace, aware of what they are doing, improve work performance and more creative in utilising the benefits of IS. Indirectly, IS users able to leave the office early and spend more time for their families and other activities. Meanwhile, the contributions of the study are two-fold: i) theoretical implication - it promotes to the new rival of theories that goes beyond the theoretical tradition of IS use; ii) practical implication - the employer has the ultimate responsibility to know the virtues and abilities of workers particularly in achieving better performance and job satisfaction. It is suggested that mindfulness theory bridging is the gap in IS innovation research as the existing models are more useful for understanding users’ intention and technology replacement decision.